PENGARUH PERKEMBANGAN SEKTOR PARIWISATA TERHADAP KESEJAHTERAAN MASYARAKAT KABUPATEN GUNUNGKIDUL DAERAH ISTIMEWA YOGYAKARTA - Badrudin, Rudy; Giri, Efraim Ferdinan; Yandra, Fachmi Pachlevi; Subiyakto, Haryono; Algifari (LPPM STIE YKPN Yogyakarta, 2024)
This study aims to examine the economic impact of tourism development on increasing community welfare in Gunungkidul Regency. Verification of the impact is carried out through community perceptions which are divided into 4 groups, namely community groups around tourist objects, local government groups, groups of business actors around tourist objects, and groups of visitors to tourist objects. Based on the results of research and discussion, it is concluded that the existence of tourist objects, promotion of tourist objects, and the role of the community affect employment; the existence of tourist objects, promotion of tourist objects, and the role of the community in influencing economic activity; the existence of tourist objects, promotion of tourist objects, and the role of the community do not affect the negative impacts of tourism; and employment and economic activity affect people's income, while the negative impact of tourism does not affect people's income.